Phenotypic Characterization of a Novel Human Alzheimer’s Disease Model to Study Microglia - Hallin, Kajsa; Svärd, Linnéa (My University, 2025)
Alzheimer’s disease (AD) is the most prevalent form of dementia and accounts for approximately 60-70% of all dementia cases [1]. The pathological hallmarks of AD include the accumulation of amyloid-β plaques and tau tangles [1]. In addition to these hallmark features, neuroinflammation plays a crucial role in the progression of the disease [2]. Microglial cells, the brain’s resident immune cells, are key players in neuroinflammatory processes [2]. In response to external and internal stimuli, they transform into different states, each characterized by distinct phenotypic changes [2]. Given their central role in mediating neuroinflammation and their sensitivity to disease-related biomarkers, it is expected that AD significantly influences the microglial phenotype. In this study, we developed and evaluated a novel human cell model to investigate changes in microglial phagocytic activity, gene expression, and morphology when cultured in cerebrospinal fluid (CSF) derived from AD patients. Human-induced pluripotent stem cell-derived microglia and cortical neurons were seeded into monocultures and cocultures, followed by incubation in CSF from AD and non-AD (CTRL) patients. The cell model was then analyzed using various functional assays, qPCR, and a morphology analysis pipeline for ImageJ and RStudio. The results showed that CSF exposure had no adverse effects on microglial viability or proliferation, supporting the model’s robustness. While qPCR and phagocytosis assays indicated increased activation in AD-CSF-treated microglia compared to CTRL-CSF, no morphological differences were observed between these groups. Instead, pronounced differences in morphology were detected between the CSF-treated and coculture media (CoM) treated conditions, highlighting the influence of CSF-derived substances on microglial morphology. These results demonstrate that the cell model can be used to study microglial phenotypic changes when cultured in AD-CSF and CTRL-CSF. However, additional analyses are needed to detect morphological differences between microglia exposed to AD- and CTRL-C.